2012
DOI: 10.5539/ijbm.v7n9p75
|View full text |Cite
|
Sign up to set email alerts
|

New Conceptual Model on Cluster Competitiveness: A New Paradigm for Tourism?

Abstract: Tourism, one of fastest growing industry and the main source of foreign income for appreciable number of developing countries, bonds people to inspire nature, culture and heritage and experiences. Decade of 90's, Crouch and Ritchie developed a conceptual model combining attributes of Porter's Diamond model, Dwyer and Kim (2003) introduced an integrated model combining Diamond and Crouch and Ritchie models integrating endowed, created and supporting resources, destination management, government and industry spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…This data is reinforced by the analysis that puts various supporting factors that are considered more important than that of features of tourism objects. According to Fernando and Long (2012), modern tourism is "experience" oriented, based on competitiveness rather than comparative scenic beauty in a destination. Therefore, ABC features provided by North Sulawesi must be understand only as foundation for competitiveness.…”
Section: Resultsmentioning
confidence: 99%
“…This data is reinforced by the analysis that puts various supporting factors that are considered more important than that of features of tourism objects. According to Fernando and Long (2012), modern tourism is "experience" oriented, based on competitiveness rather than comparative scenic beauty in a destination. Therefore, ABC features provided by North Sulawesi must be understand only as foundation for competitiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Even though some tourists may stay in a destination for a long time, few may contribute to conservation, hence, the community itself needs to be involved in conserving the environmental resources (Fernando & Long, 2012). Past research (e.g., Stronza & Gordillo, 2008; has demonstrated that local community involvement and support for environmental conservation of tourism destinations produces better outcomes than the inclusion of other stakeholders.…”
Section: Community Support Moderates Environmental Constructs and Desmentioning
confidence: 99%
“…Armenski et al (2011) pointed out, the complexity of the term "competitiveness" is become apparent that attempt to define and measure, and there can see different models both objective and /or subjective measures created. As pointed out by the scholars ,developing country arena, competitive strategies embedded with innovations will way forward towards economic prosperity, (Fernando & Long, 2012;Fernando, 2013).…”
Section: Materials Studiedmentioning
confidence: 99%